Estimation and out-of-sample Prediction of Sudden Stops : Do Regions of Emerging Markets Behave Differently from Each Other? - Comelli, Fabio (IMF Working Papers; Working Paper ;, 2015)
We identify episodes of sudden stops in emerging economies and estimate the probability to observe them. Sudden stops are more likely when global growth falters, risk aversion in financial markets rises, and vulnerabilities in the external and financial sectors increase. However, the significance of the explanatory variables vary across regions. In Latin America and Eastern Europe, gross capital inflows are more responsive to changes in global growth than in Asia. Trade linkages tend to be more important than financial linkages in Eastern Europe, while in Asia and Latin America the opposite is true. The model captures only a third of sudden stops outside the estimation sample, but issues reliable sudden stop signals.